A violência e a banalização da legislação penal - (:unkn) unknown (Universidade Federal do Pampa, 2014)
Currently has verified the exacerbation of punishments and issues increasingly constants in criminalizing laws. The increased violence is one of the justifications for this increasingly constant phenomenon. For this reason, the criminal law has been trivialized, moving away from its guiding principles, namely, that of the ultima ratio, subsidiarity and fragmentariedade. Within this context, we will compare the minimum and the maximum criminal law criminal law, foray into motion Law and Order and the Criminal Law of the Enemy. Thus, we intend to demonstrate that violence, although not the only factor, has great influence on this phenomenon, however, that criminal law should be reserved for especially relevant hypotheses.
Keywords: Direito Penal; Violência; Excesso de leis; Criminalização; Intervenção minima; Criminal Law; Violence; Excess laws; Criminalization; Minimal intervention; CNPQ::CIENCIAS SOCIAIS APLICADAS